EFEKTIVITAS SISTEM DATABASE DI DALAM SISTEM INFORMASI MANAJEMEN - Dinda Aulia; Ita Ayu Anggina Telaumbanua; Wan Frisca Putri; M. Aulia Wijaya; Nurbaiti (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2023)
This study analyzes the adequacy of databases in administration data frameworks. Analysts utilize subjective inquire about strategies. Within the information collection handle, it is separated into a few sorts of information collection strategies such as perception, writing ponder and visual investigation. The comes about of this ponder that;. The database framework plays an imperative part in a administration data framework where the database framework acts as a SIM component, SIM foundation, SIM assets, compelling SIM offices and viable SIM strategies. The database is exceptionally valuable for administration data frameworks, in case the database is well seen by clients or customers at that point it can improve quality which plays a really critical part in a framework administration data framework where the database framework capacities as a administration data component. Administration data frameworks and framework .